Motor Disabilities or Limitations An Individualized Program - Vodola, Thomas M.; Ocean Township Board of Education, Oakhurst, NJ. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
As one of the components of the Project ACTIVE (All Children Totally Involved Exercising) Teacher Training Model Kit, the manual is designed to enable the educator to organize, conduct, and evaluate individualized-personalized physical education programs for children (prekindergarten through high school) with motor disabilities or limitations. An introductory chapter includes definitions and criterion-referenced objectives which provide a basis for evaluating student and teacher performance. In Chapter II, procedures for testing, assessing, prescripting, and evaluating the physical fitness and motor performance of children are outlined and an instrument for gathering information related to the self-esteem of students in the program is provided. Recommended in Chapter III are learning experiences to involve both the students and teacher in the training program. Described in Chapter IV are tasks and activities intended to provide exercises directed to all parts of the body. Appended materials include a motor disabilities/limitations flow chart and activity checklist, a glossary, and a behavioral performance chart. (SBH)
Availability: Township of Ocean School District, Dow Avenue, Oakhurst, New Jersey 07755 ($4.00).
Sponsoring Agency: Bureau of Elementary and Secondary Education (DHEW/OE), Washington, DC.
ERIC Note: The document is one of the "Developmental and Adapted Physical Education" series; For related information see, EC 101 553-561; Some parts may reproduce poorly.
Educational level discussed: Elementary Secondary Education.
Educational level discussed: Preschool Education.
May also be available online. Address as at 14/8/18
Keywords: Adapted Physical Education; Diagnostic Teaching; Elementary Secondary Education; Exercise (Physiology); Individualized Programs; Learning Activities; Motor Development; Nonprofit Organizations; Physical Disabilities; Preschool Education; Student Evaluation; Teaching Guides; Project ACTIVE; Guides, General